Identification and Characterization of Three New Components of the mSin3A Corepressor Complex - Fleischer, Tracey C. (American Society for Microbiology, 2003)
The mSin3A corepressor complex contains 7 to 10 tightly associated polypeptides and is utilized by many transcriptional repressors. Much of the corepressor function of mSin3A derives from associations with the histone deacetylases HDAC1 and HDAC2; however, the contributions of the other mSin3A-associated polypeptides remain largely unknown. We have purified an mSin3A complex from K562 erythroleukemia cells and identified three new mSin3A-associated proteins (SAP): SAP180, SAP130, and SAP45. SAP180 is 40% identical to a previously identified mSin3A-associated protein, RBP1. SAP45 is identical to mSDS3, the human ortholog of the SDS3p component of the Saccharomyces cerevisiae Sin3p-Rpd3p corepressor complex. SAP130 does not have detectable homology to other proteins. Coimmunoprecipitation and gel filtration data suggest that the new SAPs are, at the very least, components of the same mSin3A complex. Each new SAP repressed transcription when tethered to DNA. Furthermore, repression correlated with mSin3A binding, suggesting that the new SAPs are components of functional mSin3A corepressor complexes. SAP180 has two repression domains: a C-terminal domain, which interacts with the mSin3A-HDAC complex, and an N-terminal domain, which functions independently of mSin3A-HDAC. SAP130 has a repression domain at its C terminus that interacts with the mSin3A-HDAC complex and an N-terminal domain that probably mediates an interaction with a transcriptional activator. Together, our data suggest that these novel SAPs function in the assembly and/or enzymatic activity of the mSin3A complex or in mediating interactions between the mSin3A complex and other regulatory complexes. Finally, all three SAPs bind to the HDAC-interaction domain (HID) of mSin3A, suggesting that the HID functions as the assembly interface for the mSin3A corepressor complex.